Hubungan Minat Belajar Dengan Hasil Belajar Fisika Kelas XI MIPA SMA Negeri 4 Kota Jambi - Riska Fitriani; Yetri Erna (Journal Evaluation in Education (JEE), 2022)
This study aims to determine whether there is a positive and significant relationship between interest in learning and physics learning outcomes for students in class XI MIPA at SMA Negeri 4 Jambi city. This research is a descriptive quantitative correlational type. The independent variable used in this study is interest in learning physics while learning outcomes are the dependent variable. The population used is students of class XI MIPA 1, XI MIPA 2, and XI MIPA 3 SMA Negeri 4 Jambi city. The sampling technique used is non-probability sampling, namely a sample with a 90% confidence level with a sample size of 60 students. The data collection instrument used a questionnaire and test questions. Technical analysis of prerequisite test data carried out include normality test, homogeneity test, linearity test with the help of SPSS 21 software. The results of hypothesis testing using product moment correlation test with the help of SPSS 21 software at 95% significance level = 0.05 n = 60 obtained value Pearson correlation 1 means that there is a correlation between interest and learning outcomes, then H0 is rejected. This means that H1 is accepted, that is, there is a positive and significant relationship between perceptions and learning outcomes of physics students in class XI MIPA 1, XI MIPA 2, and XI MIPA 3 in high school. State 4 Jambi City.